2019
DOI: 10.2147/jpr.s171013
|View full text |Cite
|
Sign up to set email alerts
|

<p>APOLLO-1: a randomized placebo and active-controlled phase III study investigating oliceridine (TRV130), a G protein-biased ligand at the &micro;-opioid receptor, for management of moderate-to-severe acute pain following bunionectomy</p>

Abstract: Purpose: Oliceridine is a novel G protein-biased µ-opioid receptor agonist designed to provide intravenous (IV) analgesia with a lower risk of opioid-related adverse events (ORAEs) than conventional opioids. Patients and methods: APOLLO-1 (NCT02815709) was a phase III, double-blind, randomized trial in patients with moderate-to-severe pain following bunionectomy. Patients received a loading dose of either placebo, oliceridine (1.5 mg), or morphine (4 mg), followed by demand doses via patient-controlled analges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 32 publications
8
128
0
3
Order By: Relevance
“…The findings on the lower rates of OIRD in the oliceridine cohort compared to CO cohort using IV morphine alone or combined with conventional opioids are consistent with those observed in randomized clinical phase 3 trials of patients following a bunionectomy or abdominoplasty procedure, where a reduced rate of respiratory events was reported with IV oliceridine compared with morphine [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The findings on the lower rates of OIRD in the oliceridine cohort compared to CO cohort using IV morphine alone or combined with conventional opioids are consistent with those observed in randomized clinical phase 3 trials of patients following a bunionectomy or abdominoplasty procedure, where a reduced rate of respiratory events was reported with IV oliceridine compared with morphine [ 17 , 18 ].…”
Section: Discussionsupporting
confidence: 77%
“…Findings from the ATHENA trial demonstrated that oliceridine, administered alone or as a component of multimodal analgesia, was generally safe and well tolerated in both surgical and medical patients experiencing moderate to severe acute pain, with nausea (18%), vomiting (7%), and constipation (6%) being the most frequent AEs “probably” or “possibly” related to oliceridine [ 19 ], similar to the profile observed in the prior phase 3 controlled trials [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…These clinical results suggest that oliceridine promotes effective, rapid analgesia in patients with postoperative pain, with acceptable safety/tolerability profiles and a potentially wider therapeutic window than morphine [ 48 ]. Moreover, favorable analgesia over respiratory depression has been reported for oliceridine, but not morphine in a recent study that reanalyzed data obtained from healthy volunteers and postoperative patients [ 49 ] Finally, the analgesic effectiveness and favorable safety/tolerability profiles of oliceridine regarding respiratory and gastrointestinal adverse effects compared to morphine have been confirmed in different Phase III studies [ 50 , 51 , 52 ]. In October 2018, the FDA Advisory Committee voted 8 against and 7 in favor of the approval of oliceridine for the management of moderate to severe acute pain.…”
Section: Pharmacological Studies—are Mu-receptor Agonists Biased Tmentioning
confidence: 99%